2023
DOI: 10.1590/1983-1447.2023.20210334.en
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload in oncological intensive care in the COVID-19 pandemic: retrospective cohort

Abstract: Objective: To compare the nursing workload in an oncology intensive care unit according to the condition of COVID-19 infection. Method: A retrospective cohort study. The Nursing Activities Score was used to measure the workload and document analysis for data extraction. The medical records were divided into a group of patients with COVID-19 and another group of patients without the infection. Results: The values of the Nursing Activities Score were not different depending on the sociodemographic variables, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…provocó un aumento de 20,54 puntos en el puntaje NAS, en comparación con el tratamiento quirúrgico (35) .…”
Section: Discussionunclassified
“…provocó un aumento de 20,54 puntos en el puntaje NAS, en comparación con el tratamiento quirúrgico (35) .…”
Section: Discussionunclassified
“…A retrospective cohort study involving 24,344 individuals diagnosed with TB revealed numerous vulnerabilities associated with treatment follow-up and completion in Brazil. However, the directly observed treatment [DOT], a strategy advocated by the Ministry of Health for HP, can reduce the chances of treatment loss by up to 54% [95% con dence interval -CI95%: 50-57] [23] . Additionally, income transfer actions such as the 'Programa Bolsa Família' also appear to in uence treatment adherence [3,7] .…”
Section: Discussionmentioning
confidence: 99%